Social Progress Through Community Development (New York : United Nations Bureau of Social Affairs, 1955)
A report of the Economic and Social Council and the Social Commission of the United Nations focusing on community development.
lje 04/07/17
Loans
Keywords: United Nations; Social Polic; Community development